At the Top of the Grand Staircase : The Late Cretaceous of Southern Utah - Loewen, Mark A.; Titus, Alan L. (Alan Lee), 1964- (Book collections on Project MUSE., 2013)
Presents a total synthesis of the ecology and evolution of the Late Cretaceous ecosystems of western North America by examining the research efforts and discoveries of paleontologists in the Grand Staircase-Escalante National Monument. The research documented in this book is rewriting our understanding of Late Cretaceous paleobiogeography and dinosaur phyletics.